Economic effects of litigation risk on corporate disclosure and innovation - Schantl, Stefan F.; Wagenhofer, Alfred (Review of Accounting Studies, 2024)
Empirical studies on the relationship between shareholder litigation and corporate disclosure obtain mixed results. We develop an economic model to capture the endogeneity between disclosure and litigation. Equilibrium disclosure is determined by two countervailing effects of litigation, a deterrence effect and an insurance effect. We derive four key results. (i) Decreasing litigation risk leads to less disclosure of very bad news, due to a weakening of the deterrence effect, but to more disclosure of weakly bad news, due to a weakening of the insurance effect. (ii) Given a sufficiently large information asymmetry, litigation risk dampens (boosts) overall disclosure of bad news for low (high) litigation risk firms. (iii) Capital markets respond more to the disclosure of bad news than of good news if the deterrence effect is strong, which arises if both insiders’ penalties and litigation risk are high. (iv) In an extension, we highlight real effects of litigation on corporate innovation and establish that innovation first decreases and then increases (strictly decreases) with litigation risk if insiders’ penalties are small (large). We reconcile our findings with results from a large set of U.S.-based empirical studies and make several novel predictions.